Detection of extensive cross-neutralization between pandemic and seasonal A/H1N1 Influenza Viruses using a pseudotype neutralization assay. - Béatrice Labrosse; Mathieu Tourdjman; Raphaël Porcher; Jérôme LeGoff; Xavier de Lamballerie; François Simon; Jean-Michel Molina; François Clavel (PLoS ONE, 2010)
Background Cross-immunity between seasonal and pandemic A/H1N1 influenza viruses remains uncertain. In particular, the extent that previous infection or vaccination by seasonal A/H1N1 viruses can elicit protective immunity against pandemic A/H1N1 is unclear. Methodology/principal findings Neutralizing titers against seasonal A/H1N1 (A/Brisbane/59/2007) and against pandemic A/H1N1 (A/California/04/2009) were measured using an HIV-1-based pseudovirus neutralization assay. Using this highly sensitive assay, we found that a large fraction of subjects who had never been exposed to pandemic A/H1N1 express high levels of pandemic A/H1N1 neutralizing titers. A significant correlation was seen between neutralization of pandemic A/H1N1 and neutralization of a standard seasonal A/H1N1 strain. Significantly higher pandemic A/H1N1 neutralizing titers were measured in subjects who had received vaccination against seasonal influenza in 2008-2009. Higher pandemic neutralizing titers were also measured in subjects over 60 years of age. Conclusions/significance Our findings reveal that the extent of protective cross-immunity between seasonal and pandemic A/H1N1 influenza viruses may be more important than previously estimated. This cross-immunity could provide a possible explanation of the relatively mild profile of the recent influenza pandemic.